2017
DOI: 10.3892/ol.2017.7391
|View full text |Cite
|
Sign up to set email alerts
|

IL‑8 is upregulated in cervical cancer tissues and is associated with the proliferation and migration of HeLa cervical cancer cells

Abstract: Abstract. serves an important function in chronic inflammation and cancer development; however, the underlying molecular mechanism(s) of IL-8 in uterine cervical cancer remains unclear. The present study investigated whether IL-8 and its receptors [IL-8 receptor (IL-8R)A and IL-8RB] contributed to the proliferative and migratory abilities of HeLa cervical cancer cells, and also investigated the potential underlying molecular mechanisms. Results demonstrated that IL-8 and its receptors were detected in HeLa ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…IL-33 promotes cellular proliferation and invasion in ovarian cancer by activating ERK1/2, as demonstrated by the complete abrogation of these responses in cells treated with the ERK inhibitor U0126 [52]. Moreover, ERKs mediate proliferation and/or migration in response to IL-8 in pancreatic [53] and cervical [54] cancer, to IL-34 in colon cancer cells [55], and to IL-13 in glioblastoma multiforme [56], working as downstream collectors of the pro-tumorigenic inputs of different cytokines.…”
Section: Erks Favor An Aggressive Phenotype In Tumors In Response mentioning
confidence: 99%
“…IL-33 promotes cellular proliferation and invasion in ovarian cancer by activating ERK1/2, as demonstrated by the complete abrogation of these responses in cells treated with the ERK inhibitor U0126 [52]. Moreover, ERKs mediate proliferation and/or migration in response to IL-8 in pancreatic [53] and cervical [54] cancer, to IL-34 in colon cancer cells [55], and to IL-13 in glioblastoma multiforme [56], working as downstream collectors of the pro-tumorigenic inputs of different cytokines.…”
Section: Erks Favor An Aggressive Phenotype In Tumors In Response mentioning
confidence: 99%
“…This indicates that RANKL may stimulate cervical cancer growth by activation of the IL-8 pathway. Jia et al recently showed that the expression of IL-8 was significantly higher in cervical carcinoma samples compared to normal controls and that migration and proliferation of Hela cells increased after treatment with IL-8 [69]. Survival of cervical cancer patients with high intratumoral IL-8 expression is significantly worse compared to patients with low IL-8 in their tumors [70].…”
Section: Rank-mediated Signaling and Cervical Cancermentioning
confidence: 99%
“… 18 Multiple cervical cancer cell lines have been shown to synthesize and secrete IL-6/8 in vitro. 20 , 21 IL-6 and IL-8 are multifunctional cytokines that regulate inflammation and cancer development. 20 , 22 24 Increasing evidence demonstrates that IL-6/8 plays a vital role in the pathogenesis of cervical cancer.…”
Section: Introductionmentioning
confidence: 99%